Analysis of Car Rental Practices According to Law No. 22 of 2009 and Sharia Economic Law: Rental Practice, CV. Gallery Rental, Sharia Economic Law - Syarif, Muhammad; Hasbi, Husnaini; Littaqwani, Tasya; Chaliddin, Chaliddin (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2023)
Leasing is a right commonly exercised by the community and is one form of interaction that is often carried out. The problem in this study is about the practice of Car Rental according to Law Number 22 of 2009 concerning traffic rules and Sharia Economic Law that occurs at CV Galeri Rental in Banda Sakti District, Lhokseumawe City. The formulation of this research problem, namely: 1) How is the practice of car rental at CV Galeri Rental Lhokseumawe City? 2) How is the analysis of sharia economic law and Law 22 of 2009 concerning traffic offences on car rental practices at CV Galeri Rental? This research is field research, using qualitative research methods. The approach method in this research uses empirical-juridical method. The techniques used in collecting data in this research are through observation, interviews and documentation. The results of the research show that the provisions regarding rights and obligations in the implementation of car leases at CV Galeri Rental are contained in a lease agreement in which the terms and conditions including rights and obligations are regulated. Case settlement due to negligence by the tenant in the car rental agreement at CV Galeri Rental in the form of damage or delay, the rental party refers to the agreement letter owned by CV Galeri Rental. In accordance with Law Number 22 Year 2009 Article 234. According to the view of Sharia Economic Law on the practice of Leasing, the original law is mubah (permissible), as long as it does not conflict with the rules set out in the Quran, Hadith and Ijma'. Likewise, the practice of car rental leasing that occurs at CV Galeri Rental Lhokseumawe City is also permissible, because the lease and the benefits are good for both the tenant and the renting party. But in the practice of renting a car rental, the renting party does not determine the rental time limit, but depends on the car renter how many days he wants to rent out his car.